Experimental research of power characteristics car Toyota Prius in the mode electromobile - Smyrnov, O.; Klymenko, S.; Смирнов, О. П.; Клименко, С. И.; Клименко, С. І. (Харківський національний автомобільно-дорожній університет, 2014)
It is spent experimental researches of power characteristics of the hybrid car of Toyota Prius in a car mode. It was produced by the calculation consumed electric energy, that consumes the Toyota Prius at 1 km run at different speeds. The basic purpose of the traction storage battery as part of hybrid power-plant of Toyota Hybrid System is defined.
Экспериментальное исследование энергетических характеристик автомобиля Toyota Prius в режиме электромобиля
Експериментальне дослідження енергетичних характеристик автомобіля Toyota Prius у режимі електромобіля
Keywords: Toyota Prius; high-voltage battery; electric traction; electric; hybrid power plant Toyota Hybrid System,; power characteristics; высоковольтная аккумуляторная батарея; электрическая тяга; электромобиль; гибридная силовая установка Toyota Hybrid System; энергетические характеристики; високовольтна акумуляторна батарея; електрична тяга; електромобіль; гібридна силова установка Toyota Hybrid System; енергетичні характеристики; 629.3